2019
DOI: 10.1101/600114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring shared responses across subjects using intersubject correlation

Abstract: Our capacity to jointly represent information about the world underpins our social experience. By leveraging one individual's brain activity to model another's, we can measure shared information across brains-even in dynamic, naturalistic scenarios where an explicit response model may be unobtainable.Introducing experimental manipulations allows us to measure, for example, shared responses between speakers and listeners, or between perception and recall. In this tutorial, we develop the logic of intersubject c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
212
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(217 citation statements)
references
References 141 publications
5
212
0
Order By: Relevance
“…We computed spatial pattern inter-subject correlation (pISC) Nastase et al, 2019) in the Intact Story condition for each of 400 parcels from an independent whole-brain resting-state parcellation (Schaefer et al, 2018). Controls-vs-controls pISC was calculated in the following way.…”
Section: Parcellation Pattern Similarity Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…We computed spatial pattern inter-subject correlation (pISC) Nastase et al, 2019) in the Intact Story condition for each of 400 parcels from an independent whole-brain resting-state parcellation (Schaefer et al, 2018). Controls-vs-controls pISC was calculated in the following way.…”
Section: Parcellation Pattern Similarity Mapsmentioning
confidence: 99%
“…First, we established the regions where control participants exhibited similar brain activity patterns with each other while listening to the intact narrative by calculating pattern similarity in every parcel (Schaefer et al, 2018) across the brain. Previous fMRI studies of the temporal integration hierarchy have largely used temporal ISC (tISC; e.g., Hasson et al, 2008;Lerner et al, 2011;Simony et al, 2016); here we use spatial pattern ISC (pISC; e.g., Chen et al, 2017;Oedekoven et al, 2017;Baldassano et al, 2018;Nastase et al, 2019) which allows estimates of response reliability to be calculated at each TR. The two are closely related but not redundant ((Nastase et al, 2019); Supplementary Figure 4).…”
Section: A's Neural Responses To An Auditory Narrative Match the mentioning
confidence: 99%
“…The second objective is to be flexible enough to accurately represent the organization of an individual brain. Simultaneously achieving these two objectives is challenging, in part due to inter-subject variability [1][2][3] , which is also associated with measures of cognitive performance [4] . In addition, it has also become apparent that brain functional connectivity substantially reorganizes dynamically [5] according to different cognitive states [6] .…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating dual-fMRI data in a model-free, hypothesis-free manner, whereby no a priori assumptions are made, these techniques are more appropriate for the nonlinear, unpredictable dynamic of naturalistic social exchange (Nastase, Gazzola, & Keysers, 2019). By evaluating dual-fMRI data in a model-free, hypothesis-free manner, whereby no a priori assumptions are made, these techniques are more appropriate for the nonlinear, unpredictable dynamic of naturalistic social exchange (Nastase, Gazzola, & Keysers, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven techniques have been developed to provide an alternative way of analyzing hyperscanning data, offering a means to address these outstanding questions. By evaluating dual-fMRI data in a model-free, hypothesis-free manner, whereby no a priori assumptions are made, these techniques are more appropriate for the nonlinear, unpredictable dynamic of naturalistic social exchange (Nastase, Gazzola, & Keysers, 2019). Recently, Bilek et al (2015Bilek et al ( , 2017 demonstrated how two such data-driven techniques can be combined to investigate neural coupling during social interaction.…”
mentioning
confidence: 99%